Historical developments of the Albanian language in Rahovec - Dulaj, Fridrik (Technium Social Sciences Journal, 2022)
Before we go further it is important to see the possible origin of Rahovac/ Rahovec language. If we refer the history of Rrahovec/ Rahovecas an urban center, as a starting point we can consider residences that are found in the work of Selami Puhales where we mentioned before we have two sorts of Rahovec, great Rahovec/ Rahovec and small Rahovec. Both of them had 43 headed houshold1. Its development and transformation in a small town ocured later. Recalling that only 500 families were in Rahovec/ Rahovec in 18922. Albanians for the sake of developing their economy and comerce, perhaps to preverse their physical beign, started to communicate in the language of those who supplied Rahovec/ Rahovec with goods and who governed in the administrative sense. The need for business development pushed citizens of Rahovec/ Rahovec to subject the pressure of the language of those which whom they had intercourses. Albanian language was a native languagein Rahovec/ Rahovec clearly speak some old Albanian remants like the preservation of consonant groups: mb, nd, ng3, ex. How is it going! (Puna e mbarë), Doing well! (Mbarë paq), Plant wheat! (mbjell grurë), Thanks, l exchange grapes with beans, don’t mention, eating breead (hanger buk), l load wood (ngarkoj dru) etc.